From ivory towers to international business: are universities export ready in their recruitment of international students? - Naidoo, Vik (Sage Publications, Inc, 2010)
The main hypothesis examined in this study is that the success of export recruitment strategies of universities is partly determined by their export readiness, defined as a function of market orientation. This article seeks to fulfil both a research and a practitioner gap in the export of education field. There currently exists a lack of research and discussion concerning the business aspects of export education. Suspicion of the commercial aspects of what is essentially a public good is suggested as a possible reason for this absence of research. With the commercialisation of education growing at the phenomenal rate that it currently is, it is largely time that this research gap be addressed. This study provides an important contribution by examining the export readiness of universities, in particular pre-export market orientation, and its impact on subsequent export recruitment performance.